Relative Contributions of Biodiversity and Environment to Benthic Ecosystem Functioning - Belley, Rénald; Snelgrove, Paul V. R. (Frontiers in Marine Science, 2016)
Current concern about biodiversity change associated with human impacts has raised scientific interest in the role of biodiversity in ecosystem functioning. However, studies on this topic face the challenge of evaluating and separating the relative contributions of biodiversity and environment to ecosystem functioning in natural environments. To investigate this problem, we collected sediment cores at different seafloor locations in Saanich Inlet and the Strait of Georgia, British Columbia, Canada, and measured benthic fluxes of oxygen and five nutrients (ammonium, nitrate, nitrite, phosphate, and silicate). We also measured 18 environmental variables at each location, identified macrofauna, and calculated a suite of species and functional diversity indices. Our results indicate that, examined separately, macrobenthic functional richness (FRic) predicted benthic flux better than species richness, explaining ~ 20% of the benthic flux variation at our sites. Environmental variables and functional diversity indices collectively explained 62.9% of benthic flux variation, with similar explanatory contributions from environmental variables (21.4%) and functional diversity indices (18.5%). The 22.9% shared variation between environmental variables and functional diversity indices demonstrate close linkages between species and environment. Finally, we also identified funnel feeding as a key functional group represented by a small number of species and individuals of maldanid and pectinariid polychaetes, which disproportionately affected benthic flux rates relative to their abundance. Our results indicate the primary importance of environment and functional diversity in controlling ecosystem functioning. Furthermore, these results illustrate the consequences of anthropogenic impacts, such as biodiversity loss and environmental changes, for ecosystem functioning.